2013
DOI: 10.4161/psb.23279
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous melatonin affects photosynthesis in characeaeChara australis

Abstract: Melatonin was found in the fresh water characeae Chara australis. The concentrations (~4 μg/g of tissue) were similar in photosynthesizing cells, independent of their position on the plant and rhizoids (roots) without chloroplasts. Exogenous melatonin, added at 10 μM to the artificial pond water, increased quantum yield of photochemistry of photosystem II by 34%. The increased efficiency appears to be due to the amount of open reaction centers of photosystem II, rather than increased efficiency of each reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 31 publications
9
60
0
Order By: Relevance
“…Therefore, keeping photosynthetic organ in good conditions is important to enhance plant tolerance to stress factors by lowering oxidative damage. Lazár et al (2013) found that exogenous melatonin could significantly increase photosynthesis in characeae Chara australis, which was due to the protection of melatonin against ROS for chlorophylls and photosynthetic proteins. In this study, we observed that melatonin significantly increased chlorophyll content and the maximal photochemical yield of PSII (Fv/Fm) under sodic alkaline stress, The Fv/Fm ratio is an index of the maximum photochemical efficiency of PSII in the dark-adapted state and a decrease in this parameter is a reliable sign of photoinhibition, and it also provides valuable information on light driven ROS generation and ROS detrimental effects on photosynthetic activity (Hideg and Schreiber, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, keeping photosynthetic organ in good conditions is important to enhance plant tolerance to stress factors by lowering oxidative damage. Lazár et al (2013) found that exogenous melatonin could significantly increase photosynthesis in characeae Chara australis, which was due to the protection of melatonin against ROS for chlorophylls and photosynthetic proteins. In this study, we observed that melatonin significantly increased chlorophyll content and the maximal photochemical yield of PSII (Fv/Fm) under sodic alkaline stress, The Fv/Fm ratio is an index of the maximum photochemical efficiency of PSII in the dark-adapted state and a decrease in this parameter is a reliable sign of photoinhibition, and it also provides valuable information on light driven ROS generation and ROS detrimental effects on photosynthetic activity (Hideg and Schreiber, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…MT, as an antioxidant, can prevent the degradation of chlorophyll [8] and protect the photosynthetic systems [9]. Under high-temperature stress, MT increases the chlorophyll content, the primary light energy conversion efficiency of cucumber seedlings; thereby, improving their photosynthetic capacity [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have proposed roles for MEL and 5HT in mediation of stress including protection of plant organelles and structures from oxidative damage caused by free radicals 16,[34][35][36] and the elimination of extraneous metabolic products through detoxification. 37 The current data are the first suggestion of synergy between cholinergic metabolism and neuroindoleamine signaling in plants.…”
Section: Iaas and Indoleaminesmentioning
confidence: 99%
“…63 In brief, the extracts were diluted (n = 6), replicated (n = 24) and randomly assigned to a 96 well microplate alongside extract blanks (n = 24), assay blanks (n = 3), negative control (n = 3), and a positive control of Trolox ((±)-6-Hydroxy-2,5,7,8-tetramethylchromane-2-carboxylic acid; Sigma, purity ≥ 97%) dilutions (1,8,16,24,32,40, and 50 µM) in triplicate. An aliquot of each extract or Trolox standard (100 µL) reacted with 100 µL of 0.1 mM DPPH for 15 min at 25 °C.…”
Section: Iaa and Indoleamine Data Analysismentioning
confidence: 99%
See 1 more Smart Citation